2019
DOI: 10.1186/s40168-019-0651-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in HIV–pneumonia patients is related to peripheral CD4 counts, lung microbiota, and in vitro macrophage dysfunction

Abstract: Pneumonia is common and frequently fatal in HIV-infected patients, due to rampant, systemic inflammation and failure to control microbial infection. While airway microbiota composition is related to local inflammatory response, gut microbiota has been shown to correlate with the degree of peripheral immune activation (IL6 and IP10 expression) in HIV-infected patients. We thus hypothesized that both airway and gut microbiota are perturbed in HIV-infected pneumonia patients, that the gut microbiota is related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…In contrast, the relative abundance in the genera identified to be more abundant in HIV-showed a trend of positive correlation with fecal microbiome alpha diversity and CD4 counts. Enrichment of Streptococcus in fecal microbiome of HIV-1 infected individuals with low CD4 counts has been reported previously (Monaco et al, 2016;Shenoy et al, 2019). The inverse correlation of relative abundance in Gemella and Streptococcus with CD4 counts in the present study (Figure 7 and Supplementary Figures 5C, D) may imply association of these bacteria with immunosuppression (Shenoy et al, 2019;Ueberroth and Roxas, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, the relative abundance in the genera identified to be more abundant in HIV-showed a trend of positive correlation with fecal microbiome alpha diversity and CD4 counts. Enrichment of Streptococcus in fecal microbiome of HIV-1 infected individuals with low CD4 counts has been reported previously (Monaco et al, 2016;Shenoy et al, 2019). The inverse correlation of relative abundance in Gemella and Streptococcus with CD4 counts in the present study (Figure 7 and Supplementary Figures 5C, D) may imply association of these bacteria with immunosuppression (Shenoy et al, 2019;Ueberroth and Roxas, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Enrichment of Streptococcus in fecal microbiome of HIV-1 infected individuals with low CD4 counts has been reported previously ( Monaco et al., 2016 ; Shenoy et al., 2019 ). The inverse correlation of relative abundance in Gemella and Streptococcus with CD4 counts in the present study ( Figure 7 and Supplementary Figures 5C, D ) may imply association of these bacteria with immunosuppression ( Shenoy et al., 2019 ; Ueberroth and Roxas, 2019 ). Furthermore, this study showed reduction of several butyrate producing bacteria including Faecalibacterium, Butyricimonas , and other members of Ruminococcaceae , known for their role in maintenance of gut homeostasis ( Furusawa et al., 2013 ), in HIV+ as previously reported ( Dillon et al., 2017 ).…”
Section: Discussionsupporting
confidence: 70%
“…Notably, these studies controlling for MSM status account for only 33% (N = 16) of the total studies (N = 48) comparing HIV+ to HIV− patients published to date [29, 50-54, 56-58, 60-64, 68, 76, 83-85, 88-100]. Several other studies variably controlled for MSM status but had no HIV-control group [15,30,32,34,38,54,66,67,69,[101][102][103][104][105][106][107][108]. Thus, the majority of published studies to date have been insufficiently controlled for the critical variable of MSM status, limiting interpretation of the data.…”
Section: Hiv and The Gut Microbiome: No Consistent Hiv-linked Dysbiosis Identified Msm Status As A Confoundermentioning
confidence: 99%
“…Rocafort and coworker 148 reported that the gut microbiota signature of recently HIV‐infected patients is characterized by a depletion of representatives from Akkermansia , Anaerovibrio , Bifidobacterium , and Clostridium . Another recent study 149 performed on a cohort of HIV‐infected pneumonia patients confirmed that the gut microbiota of HIV‐infected individuals included a high relative abundance of members from Bacteroidaceae, Enterococcaceae, Enterobacteriaceae, Ruminococcaceae, and/or Prevotellaceae in association with Ruminococcaceae representatives, and was related to the patient's CD4 + cell counts; the relatively high abundance of phylum Ruminococcaceae contrasts with that observed in previous studies. Future investigation is required to investigate whether these changes are specific to HIV infection or are simply a consequence of the gut inflammation process.…”
Section: Environmental Factors: the Microbiota In Shaping Hiv Restricmentioning
confidence: 66%